If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -1) = -2x + 22 Reorder the terms: 3(-1 + x) = -2x + 22 (-1 * 3 + x * 3) = -2x + 22 (-3 + 3x) = -2x + 22 Reorder the terms: -3 + 3x = 22 + -2x Solving -3 + 3x = 22 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -3 + 3x + 2x = 22 + -2x + 2x Combine like terms: 3x + 2x = 5x -3 + 5x = 22 + -2x + 2x Combine like terms: -2x + 2x = 0 -3 + 5x = 22 + 0 -3 + 5x = 22 Add '3' to each side of the equation. -3 + 3 + 5x = 22 + 3 Combine like terms: -3 + 3 = 0 0 + 5x = 22 + 3 5x = 22 + 3 Combine like terms: 22 + 3 = 25 5x = 25 Divide each side by '5'. x = 5 Simplifying x = 5
| 2y+3y+23=48 | | 3w^2-12=0 | | 12x-3=4x+29 | | 6x=51 | | x^2-12x-9=0 | | 2x+Y-1=0 | | 8(y-2)=2y-46 | | 2x(x-1)=162-2x | | 2w+2(3w-12)=640 | | 8.5-2.7xk=3.9xk-18.89 | | 13x-6=6x+15 | | 2(x-2)+46=-4x | | 3x+8=4x-22 | | 3(x-4)-14=2(x-7)+7 | | 3x+5y+11=4(5x-2y) | | 2x^2-3x=40 | | 13x=6x+42 | | x^6+x^2= | | 4x^2+5=20 | | x+(x+6)+2x=94 | | 6n+3=63 | | 5(3y-1)-1(2y)=10 | | x^2-37=0 | | -5x^2+10x=0 | | -3+n=-91 | | -2x=7y-19 | | -17=63+n | | 2+5*3+4= | | 35x^2+x-6=0 | | n+(-3)=-91 | | 7.32xA=13.53+2.81xA | | 9+2(x-7)=0 |